Professor's perception of the use of digital skills and gamification in a Peruvian university - Rosa Núñez-Pacheco; Aymé Barreda-Parra; Eveling Castro-Gutierrez; Osbaldo Turpo-Gebera; Ignacio Aguaded (OmniaScience, 2023)
The COVID-19 pandemic has produced profound changes in higher education, with the replacement of face-to-face instruction with distance or remote education, which involves the management of digital skills by teachers and students. The purpose of this research is to analyze the perception of professors with regard to digital skills and the use of gamified strategies in the teaching-learning process in a virtual context. A questionnaire was sent to 81 professors in different areas of knowledge at a Peruvian public university during the first academic semester of 2020. A strong correlation (r≥.700, p=.01) was found between the use of ICT and gamification as a resource for teaching-learning, and a moderate correlation between the knowledge of digital competences and the possibilities of application as part of the instructional strategies. From the results obtained, it is clear that the participants have a positive perception of digital skills and gamified strategies, regardless of academic degree or area of knowledge. This could provide support for the update of those proposals targeting professors in order to improve their digital skills.